Василь Андрійович Страдомський (1831-1902): лікар, колекціонер, громадський діяч - Морозова, О. (Краєзнавство, 2018)
У статті висвітлений життєвий шлях відомого миколаївського лікаря, громадського діяча Василя
Андрійовича Страдомського. Автор подає маловідомі аспекти біографії В. Страдомського, зокрема дані
про батьків, службову й суспільну діяльність Василя Андрійовича. Family of Stadomsky (the roots of wich dated back to medieval Poland) – one of the most well-known and famous
of his time in Mykolayiv. The Stradomsky’s family gave to Mykolayiv region many famous persons: the best
known doctors, poets, teachers, clerics, etc.
The article presents the story of the life of the famous doctor, public figure, collector Vasily Andriyovych Stradomsky.
The author presents unknown aspects of B. Stradomsky's biography, in particular data of his parents, service
and social activities.
The basic material about the representatives of the family is submitted by the fund of the Mykolayiv State Archive
№ 448 «Vasyl Andreyevich Stradomsky (1831–1902) – the senior ship-doctor of the Black Sea naval
crew» (25 cases). It contains information about the biography of Vasily Andriyovych Stradomsky, presented by his
son Borys Vasyliovych. Here you can find service records and certificates, documents on the teaching of Vasily Andriovych
in Mglynsk district school (Chernihiv province), as well also at the Kyiv University, materials on the assignment
of his titles and orders for rewards, documents – permissions for entry abroad, obituary B. A.Stradomsky
and others like that.
During his living in Mykolayiv, Vasily Andriyovych left about himself only pleasant memories. But the biggest
part of his active life the doctor has spent in work all ower the world. His calm and measured years, he spent in
Mykolayiv. В статье освещен жизненный путь известного николаевского доктора, общественного деятеля Василия Андреевича Страдомского. Автор подает малоизвестные аспекты биографии В. Страдомского, в частности данные про родителей, служебную и общественную деятельность Василия Андреевича.